IMPROVING STUDENTS’ ABILITY IN USING DEGREES OF COMPARISON OF ADJECTIVE BY USING PICTURES AT GRADE VIII MTS NURUL JIHAD TEMBILAHAN HULU - Susanti Susanti; Rahmatunnisa Rahmatunnisa (Fakultas Keguruan dan Ilmu Pendidikan, 2017)
This research aims at describing about whether or not the pictures are able to improve students’ ability in using degrees of comparison of adjective to 19 students of the grade VIII of MTs Nurul Jihad Tembilahan Hulu. In this research, the researcher conducted a research design by using CAR. The instruments used to understanding the different of pictures in form of multiple choice test, observation sheets, and interview. Based on the findings, the result of posttest on the first cycle gained 6 students (31.6%) who are able to pass the KKM by mean score 67.8. The score did not reach the criteria of successful. Meanwhile, the posttest on the second cycle gained 13 students (68.4%) who passed the KKM and derived mean score is 81.3, it has reached the criteria of successful. There was an improvement of the students’ ability in using degrees of comparison of adjective from cycle one and cycle two as much as 13.5%. Thus, the researcher did not continue to the next cycle. In addition, students’ responses to learning are generally positive. Most of them were interested and more able about the degrees of comparison of adjective. Not only by using pictures but also the ways in teaching learning able to improve students’ ability in using degrees of comparison of adjective. Based on these findings, it can be concluded that the use of pictures and the ways in teaching learning process are able to improve students’ ability in using degrees of comparison of adjective.